Pengaruh Pemberian Sayur Daun Katuk terhadap Produksi ASI Ibu Menyusui di Desa Air Balui Wilayah Kerja Puskesmas Selensen Kabupaten Indragiri Hilir - Tri Evi Jayanti; Wira Ekdeni Aifa; Rizka Mardiya; Nurhidaya Fitria (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
Low breast milk production is one of the factors causing failure of exclusive breastfeeding in infants. One non-pharmacological effort to increase breast milk production is consuming katuk leaves, which contain lactagogue compounds. This study aimed to determine the effect of giving katuk leaf vegetables on breast milk production of breastfeeding mothers in Air Balui Village, working area of Selensen Health Center, Indragiri Hilir Regency. This was a quantitative study with a Pre-Experimental design using a One Group Pretest-Posttest Design. The population was all 33 breastfeeding mothers in Air Balui Village, with a sample of 17 respondents selected using purposive sampling. The study was conducted on April 6-11, 2026. The research instrument was an observation sheet on breast milk production. Data were analyzed using univariate and bivariate analysis with the Paired Sample T-Test. Univariate results showed that before the intervention the majority of respondents had an inadequate milk production category, while after being given 100 grams of katuk leaf vegetables for 6 days the majority increased to the smooth category. The bivariate test obtained a p-value = 0.000 < α = 0.05, indicating an effect of giving katuk leaf vegetables on breast milk production of breastfeeding mothers in Air Balui Village. Breastfeeding mothers are expected to use katuk leaves as a natural alternative to help increase breast milk production.